Are immigrants overeducated in Germany? Determinants and wage effects of educational mismatch - Caroline Schwientek (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2016)
This paper investigates determinants and wage effects of educational mismatch for both natives and immigrants in Germany. Using the GSOEP panel data from 1991 to 2013, I find that conditional on educational attainment immigrants face a higher incidence of overeducation compared to their native counterparts. Among immigrants German language skills as well as education and experience gained in Germany are negatively correlated with the risk of overeducation. Results from the wage regression indicate that required education is equally rewarded for natives and immigrants, whereas immigrants suffer from a higher penalty from overeducation, but face a lower penalty from undereducation.
Keywords: I21; I26; J15; J24; J31; 330; educational mismatch; wages; immigrants